دراسة الغزارة النسبية للمنخربات والتركيب الليتولوجي للرمال الشاطئية في منطقة رأس شمرا-اللاذقية. (Latakia University Journal -Basic Sciences Series, 2017)
قمنا بدراسة مجهرية لخمس عينات من الرمال الشاطئية الحالية في شاطئ رأس شمرا, تم تحديد محتواها المنخربي وغزارة الأنواع بالنسبة لبعضها البعض, أظهرت التحاليل الميكروباليونتولوجية أن معظم الأنواع المحددة وعددها17 نوع تعيش على القاع في المياه البحرية الضحلة وبدرجات حرارة معتدلة إلى حارة نسبياً.تمثلت الغزارة الكبيرة بأنواع الاجناس القاعية : Amphistegina, Textularia, peneroplis مما يدل على توفر شروط بيئية مناسبة لازدهار هذه الأجناس وهي أقرب إلى الشروط الحالية.تتميز الرمال المدروسة بكونها مفككة, ناعمة إلى متوسطة حجم الحبات, ألوانها متنوعة وغنية ببقايا الهياكل العضوية, وبشكل رئيسي بقايا هياكل الرخويات مع وجود حصيات بيضوية بحرية المنشأ ومتنوعة الحجم.أظهرت تحاليل x.r.d وجود طورين كلسي رئيسي وكوارتزي ثانوي, كما اظهرت دراسة الشرائح الصخرية الرقيقة المأخوذة من الصخور المنتشرة في المنطقة والتي يمكن اعتبارها صخور المصدر للرمال الموجودة في منطقة الدراسة انها عبارة عن حجر رملي كلسي.A microscopic study was done on five samples from the current beach sand at Ra’asShimra beach in order to identify their Foraminifera content and the abundance of the species relative to each other. The micropaleontology analysis showed that the majority of the 17 specified types live on the bottom in shallow marine waters at moderate to hot temperatures.The abundance of the species was noticed in the benthic species such as: Amphistegina, Textularia, and peneroplis, which indicates the availability of suitable environmental conditions for the prosperity of these species, which is close to the current conditions.The samples of sand studied are characterized by their being disjointed, small to medium in size, varying in color, and rich in organic remains, mainly the remains of molluscs, in addition to oval marine-originated stones that vary in size.The X.R.D analysis showed the presence of two phases: a major calcareous phase, and a secondary quartz phase. The study of the thin rock slides taken from rocks located in the region, which can be considered as the source rocks of sand in the study area, showed that it is a sandy limestone.